KEWENANGAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG TERKAIT PRESERVASI JALAN DI KOTA PEKANBARU BERDASARKAN PERATURAN PERUNDANG - UNDANGAN - Lukman Hakim; Dessy Artina; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Article 24 paragraph (1) of Law Number 22 of 2009 concerning Road Trafficand Transportation explains that road operators must immediately and properlyrepair damaged roads that can lead to traffic accidents. However, it is still notimplemented, especially on roads in Pekanbaru City so that many peoplecomplain because there are still a lot of road damage. The research objectives ofthis thesis are; First, the Authority of the Public Works and Spatial PlanningOffice of Pekanbaru City, Third, the efforts of the Pekanbaru City Public Worksand Spatial Planning Service.This type of research can be classified in the type of sociological juridicalresearch, because in this study the author is directly at the location or place beingstudied in order to provide a complete and clear picture of the problem beingstudied. This research was conducted at the Pekanbaru City Public Works andSpatial Planning Office, Pekanbaru City Police Traffic Unit, and Pekanbaru CityRegional Representative Council Office, while the population and sample are allparties related to the problems studied in this study, the data sources used aredata primary and secondary data, the data collection method in this study wasinterviews and literature study.From the results of the research problem, there are three main things thatcan be concluded, First, the authority of the Public Works and Spatial PlanningService towards road preservation in Pekanbaru City, Second, the factors thatbecome obstacles faced by the Public Works and Spatial Planning Office relatedto road preservation in Pekanbaru City are limited budget, lack of humanresources, limited heavy equipment, limitations in managing natural resources,the need for community initiatives when seeing roads around their homes toimmediately report when there are damaged roads, Third, the efforts of the PublicWorks and Spatial Planning Department related to road preservation inPekanbaru City is submitting a budget in accordance with the previously agreedperformance plan, adding a fleet of heavy equipment, having solutions in utilizingnatural resources, the community needs to report damaged roads so that they canbe immediately recorded for repairs.Keywords: Authority – Accident – Road Preservation